2006
DOI: 10.1158/1535-7163.mct-05-0485
|View full text |Cite
|
Sign up to set email alerts
|

PM-20, a novel inhibitor of Cdc25A, induces extracellular signal–regulated kinase 1/2 phosphorylation and inhibits hepatocellular carcinoma growth in vitro and in vivo

Abstract: We have synthesized several new phenyl maleimide compounds, which are potent growth inhibitors of several human tumor cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…13). Active site binding and cysteine-adduction by electrophilic pharmacophores was optimized based on molecular docking studies using the crystal structure of the Cdc25B catalytic domain (124,183,212). It is interesting to note that the napthoquinone menadione (vitamin K 3 ) discussed above in the context of prooxidant redox cycling (Section II.C) represents an early prototype inhibitor of Cdc25 phosphatase enzymatic activity (382).…”
Section: F Targeting Cdc25 Phosphatases: Nsc 67121 and F-nsc 67121mentioning
confidence: 99%
See 1 more Smart Citation
“…13). Active site binding and cysteine-adduction by electrophilic pharmacophores was optimized based on molecular docking studies using the crystal structure of the Cdc25B catalytic domain (124,183,212). It is interesting to note that the napthoquinone menadione (vitamin K 3 ) discussed above in the context of prooxidant redox cycling (Section II.C) represents an early prototype inhibitor of Cdc25 phosphatase enzymatic activity (382).…”
Section: F Targeting Cdc25 Phosphatases: Nsc 67121 and F-nsc 67121mentioning
confidence: 99%
“…In an attempt to further reduce ROS-induced nonspecific cellular toxicity, nonquinoid electrophilic pharmacophores that inactivate Cdc25 phosphatases by alkylation of the active (183). Equally, the redox-silent nonquinone sulfone analog of vitamin K 3 H32 inhibits hepatoma cell growth by targeting the catalytic cysteine residue of Cdc25A without involvement of ROS production (124).…”
Section: F Targeting Cdc25 Phosphatases: Nsc 67121 and F-nsc 67121mentioning
confidence: 99%
“…Mechanisms of rapid activation of the MAPKs, in particular http://bmbreports.org BMB reports ERK-1 and -2, in response to E2 are suggested to involve the actions via membrane bound ERα/β or G-protein coupled receptor 30 (GPR30). Since it has been shown that hydrogen peroxide is able to activates ERK-1/2 and inactivate Cdc25A in MCF-7 cells and both proteins form a protein complex, it is possible that ERK may be activated by inhibiting its association with Cdc25A or inactivating Cdc25A by estrogen-induced ROS (103). PI3K/Akt pathway is another signaling event regulated by estrogen-induced ROS.…”
Section: Ros-mediated Redox Signalingsmentioning
confidence: 99%
“…Furthermore, the inhibitory effect of the Cdc25a +/À background on the ras-neu oncogenic pathway supports the rationale of using CDC25A inhibitors for therapeutic intervention. Multiple small-molecule agents including vitamin K analogues have been developed as pharmacologic inhibitors of CDC25 phosphatases (43)(44)(45). One of such CDC25 inhibitors, BN82685, exhibits in vivo tumor inhibitory activity as an orally bioactive agent (46).…”
Section: Cdc25amentioning
confidence: 99%